Biosimilar biological drugs in the treatment of inflammatory bowel diseases - Magdalena Kaniewska; Piotr Eder; Anita Gąsiorowska; Maciej Gonciarz; Jarosław Kierkuś; Ewa Małecka-Panas; Grażyna Rydzewska (Gastroenterology Review)
Within the last 20 years, tumour necrosis factor inhibitors have been proven to be effective in achieving and maintaining clinical and endoscopic remission in patients with Crohn’s disease and ulcerative colitis. Since 2013, when infliximab originator lost its patent protection, patients with inflammatory bowel diseases (IBDs) in Poland have also been treated with biosimilar drugs. Biosimilars are drugs with high similarity to their reference products in terms of physicochemical properties, including structure, safety, and efficacy. Biosimilars are approved for use on the basis of the same rigorous quality standards as their reference products. In 2018, also biosimilars of adalimumab have become available. Studies published to date have shown that biosimilars do not differ from reference drugs in terms of the efficacy and safety. There are numerous data to confirm that a single switch of biological drugs (mainly from reference to biosimilar drugs) has no effect on therapy efficacy and safety. However, a significantly lower cost of therapy with biosimilars not only allows us to treat a much larger number of patients but may also necessitate multiple switches from reference drugs to biosimilars (including biosimilars produced by different manufacturers). Recently, the first results have been published concerning multiple switches in patients with psoriasis and rheumatoid arthritis. However, no such data are currently available for patients with IBDs.